Lung function, arterial saturation and oxygen uptake in elite cross country skiers: influence of exercise mode - Holmberg, H. C.; Rosdahl, H.; Svedenhag, J. (Scandinavian Journal of Medicine & Science in Sports, 2007)
Arterial desaturation during exercise is common in endurance-trained athletes, a phenomenon often more pronounced when the muscle mass engaged in the exercise is large. With this background, the present study monitored seven international-level cross country skiers performing on a treadmill while running (RUN), double poling (DP; upper body exercise) and diagonal skiing (DIA; arm and leg exercise). Static and dynamic lung function tests were performed and oxygen uptake was measured during submaximal and maximal exercise. Lung function variables (including the diffusion capacity) were only 5-20% higher than reported in sedentary men. Vital capacity was considerably lower than expected from the skiers' maximal oxygen uptake (VO2max), but the maximal ventilation followed a linear relationship with VO2max. None or only a mild desaturation was observed in DP, RUN and DIA. Blood lactate concentration was slightly higher in DIA than in DP but not different from RUN. In DIA, VO2max was 6.23±0.47 L/min (mean±SD), which was 3.8% and 13.9% higher than in RUN and DP, respectively, with similar peak heart rates for the three exercise modes. No relationships were present either between the degree of desaturation and pulmonary functions tests, or with peak oxygen uptakes. The low blood lactate accumulation during the exhaustive efforts contributed to the arterial oxygen saturation being mild in spite of the very high oxygen uptake observed in these skiers.